(untitled) (Fiep Bulletin - online, 2014)
The man health care less than women, and a thinking of invulnerability they expose themselves to more risks that favors the disease, especially chronic degenerative diseases, whose main risk factor hypertension, which already has significant values in adolescence. Exploratory, descriptive and cross-sectional quantitative approach with a sample of 47 male adolescents the afternoon shift , assessed by questionnaire , measurements of weight , height and blood pressure . Objective: To investigate the risk factors for hypertension in male adolescents in the hinterland of Paraiba . The results showed that 57.4 % of adolescents are aged between 16-17 years old, 40.4 % attend the 1st year of high school , 83 % only study , 48.9 % are brown , 93.6 % practice some physical activity , 61.7 % consume too much salt , 17 % are overweight / obese and 25 % with hypertensive values??. Concludes that it is necessary to establish preventive activities with schools to combat hypertension and its risk factors in a multidisciplinary activity, which promotes the development of normotensive adolescents.